Activation of Canine, Mouse and Human TLR2 and TLR4 by Inactivated Leptospira Vaccine Strains - Novak, Andreja; Pupo, Elder; van’t Veld, Esther; Rutten, Victor P. M. G.; Broere, Femke; Sloots, Arjen (Frontiers in Immunology, 2022)
Canine Leptospira vaccines contain inactivated strains of pathogenic Leptospira, the causative agents of leptospirosis. For an effective response to vaccination, activation of the innate immune system via pattern recognition receptors such as TLRs is crucial. However, it is not known which TLRs are activated by Leptospira in dogs. To investigate the involvement of canine TLR2, TLR4, and TLR5 in the recognition of Leptospira, we stimulated canine moDC and reporter cells expressing canine TLR2 with either whole-inactivated bacteria or purified LPS of Leptospira strains, representing the serogroups generally used in canine leptospirosis vaccines. Using the endotoxin neutralizing reagent polymyxin B and TLR4 antagonist RS-LPS, we demonstrate that Leptospira LPS and canine TLR4 are involved in IL-1β production as well as in the uptake of inactivated Leptospira in canine moDC. Furthermore, polymyxin B only partially inhibited IL-1β production induced by inactivated Leptospira, suggesting that next to TLR4, also other TLRs may be involved. The observed activation of canine TLR2-expressing reporter cells by inactivated Leptospira strains indicates that TLR2 could be one of these TLRs. Next, we analyzed TLR2 and TLR4 activating capabilities by the same Leptospira strains using human and mouse TLR-expressing reporter cells. Inactivated Leptospira and leptospiral LPS activated not only mouse, but also human TLR4 and this activation was shown to be LPS dependent in both cases. Additionally, inactivated Leptospira activated mouse and human TLR2-expressing reporter cell lines. In our study, we could not identify significant species differences in the recognition of Leptospira by TLR2 and TLR4 between dog, human and mouse. Lastly, we show that these inactivated Leptospira strains are recognized by both mouse and human TLR5 reporter cells only after exposure to additional heat-treatment. Unfortunately, we were not able to confirm this in the canine system. Our data show that TLR2 and TLR4 are involved in the recognition of Leptospira strains used in the production of canine Leptospira vaccines. This study contributes to the understanding of Leptospira-induced innate immune responses in dogs, humans, and mice. Future studies are needed to further explore the role of canine TLR2, TLR4 and TLR5 in the induction of vaccine-mediated immunity against Leptospira.